Strategic framework for developing resilience in Agri-Food Supply Chains during COVID 19 pandemic. Issue 11 (2nd November 2022) - Kumar, Pravin; Kumar Singh, Rajesh
ABSTRACT: The Agri-food Supply Chains (AFSC) dealing with perishable items have suffered a lot due to the COVID 19 pandemic. During this uncertain time, developing resiliency has become a priority for management. Therefore, the main purpose of the study is to explore the impact of COVID-19 on AFSC and the possible strategies for improving the resilience of the AFSC. Impacts on AFSC and possible strategies are explored through the literature review and experts' opinions. The importance rating of impacts of COVID-19 on AFSC is determined using the Best-Worst Method (BWM). These impacts are further correlated with the strategies for improving the resilience of AFSC using Quality Function Deployment (QFD). The findings of the study will help farmers, food processors, distributors, and retailers to maintain the uninterrupted flow of food items from farmers to end-users during the uncertain business environment. It will also contribute to formulating effective policies by the government and other stakeholders for improving the resilience of AFSCs.